2019
DOI: 10.1007/s00289-019-02717-y
|View full text |Cite
|
Sign up to set email alerts
|

Anionic ring-opening copolymerization of styrene oxide with monosubstituted oxiranes: analysis of composition of prepared new copolyether-diols by MALDI-TOF mass spectrometry

Abstract: Several new random copolyethers of styrene oxide (SO) and other monosubstituted oxirane as comonomer, i.e., propylene oxide (PO), isopropyl glycidyl ether (IPGE) or allyl glycidyl ether (AGE), were synthesized in THF solution at room temperature. As initiator monopotassium salt of dipropylene glycol activated by 18-crown-6 complexing agent was used. Synthesized copolyether-diols were characterized by SEC, 13 C NMR and MALDI-TOF techniques. They were unimodal and had M n = 3500-4600 and relatively low dispersit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Random copolymers of l -lactic acid and isosorbide succinate moieties, 96 styrene oxide (SO) and allylglycidyl ether (AGE), propylene oxide (PO) or isopropyl glycidyl ether (IPGE) 97 and poly(styrene- co -4-vinylpyridine) 98 were verified by MALDI-TOF-MS. Schubert reported characterization of different poly(2-oxazoline) block copolymers by MALDI-TOF-MS, and revealed the desired polymer structure and possible polymerization mechanisms. 99 The crossover reaction during ROMP block copolymerization of 3-methyl-3-phenylcyclopropene and norbornene derivatives was investigated using MALDI-TOF-MS by Binder et al 100 Samperi et al applied MALDI-TOF-MS to characterize the linear-hyperbranched hybrid poly(butylene adipate) (HPBA) copolymers.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random copolymers of l -lactic acid and isosorbide succinate moieties, 96 styrene oxide (SO) and allylglycidyl ether (AGE), propylene oxide (PO) or isopropyl glycidyl ether (IPGE) 97 and poly(styrene- co -4-vinylpyridine) 98 were verified by MALDI-TOF-MS. Schubert reported characterization of different poly(2-oxazoline) block copolymers by MALDI-TOF-MS, and revealed the desired polymer structure and possible polymerization mechanisms. 99 The crossover reaction during ROMP block copolymerization of 3-methyl-3-phenylcyclopropene and norbornene derivatives was investigated using MALDI-TOF-MS by Binder et al 100 Samperi et al applied MALDI-TOF-MS to characterize the linear-hyperbranched hybrid poly(butylene adipate) (HPBA) copolymers.…”
Section: Applicationsmentioning
confidence: 99%
“…85 This MS technique was also used for monitoring other homopolymers with different structures, such as poly(dendrimer)s, 86 poly(2-oxazoline), 87 poly(ethylene glycol), and allyl(1-ethoxyethoxy)-PEG-OH, 88 as well as uorotelomer-based acrylate polymers (FTACPs), 89,90 trimethylene carbonate, 91 poly(methyl methacrylate) (PMMA), 92 linear 3-polylysine, 93 poly(butoxycarbonylaminomethyl acrylate) (PtBAMA) homopolymer, 94 poly(1.2-butylene oxide)-diol (PBOdiol) 95 and so on. Random copolymers of L-lactic acid and isosorbide succinate moieties, 96 styrene oxide (SO) and allylglycidyl ether (AGE), propylene oxide (PO) or isopropyl glycidyl ether (IPGE) 97 and poly(styrene-co-4-vinylpyridine) 98 were veried by MALDI-TOF-MS. Schubert reported characterization of different poly(2oxazoline) block copolymers by MALDI-TOF-MS, and revealed the desired polymer structure and possible polymerization mechanisms. 99 The crossover reaction during ROMP block copolymerization of 3-methyl-3-phenylcyclopropene and norbornene derivatives was investigated using MALDI-TOF-MS by Binder et al 100 Samperi et al applied MALDI-TOF-MS to characterize the linear-hyperbranched hybrid poly(butylene adipate) (HPBA) copolymers.…”
Section: Characterization Of Homopolymers and Copolymersmentioning
confidence: 99%
“…The monomers were polymerized at various rates depending on the polar and steric effects of the substituent [23]. The reaction times were relatively long, which can result from intra-and/or intermolecular proton exchange between the OH and OK groups [21]. Table 1 shows data concerning the average molar masses (M n ) and dispersities (M w /M n ) of the mentioned polymers, as well as the initiator efficiency (f = M calc /M n ) for complete conversion of the monomer.…”
Section: Homopolyether-diolsmentioning
confidence: 99%
“…In general, the 13 C NMR spectra of copolymers reveal strong signals of carbons present in polymer chains (CH 2 and CH) and substituents, as well as weak signals in carbons' terminal groups (Table 7). Weak signals of CH 3 carbons derived from initiator were observed in the 13 C NMR spectrum at 17.3 ppm of copolymers (21) and (23). The lack of signals from the terminal carbon of the CH(CH 3 )OH group from the initiator at 65.0 and 67.1 ppm indicated that propagation occurs in two directions.…”
Section: Random Copolyether-diolsmentioning
confidence: 99%